2023
DOI: 10.3389/fmicb.2023.1288525
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the causal association between gut microbiota and intrahepatic cholangiocarcinoma through Mendelian randomization analysis

Zhitao Chen,
Weiguang Shi,
Kailei Chen
et al.

Abstract: BackgroundIntrahepatic cholangiocarcinoma (ICC) is an aggressive liver cancer with poor prognosis. The gut microbiota has been linked to ICC, but evidence for causality is lacking. Elucidating causal gut microbiota-ICC links could inform prevention and treatment strategies.Materials and methodsWe performed a bidirectional two-sample Mendelian randomization (MR) study to investigate causal associations between gut microbiota and ICC risk. Genome-wide significant single nucleotide polymorphisms (SNPs) associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that a high-fat diet (HFD) and Clostridium difficile infection (CDI) can decrease the abundance of Parasutterella in the gut ( 90 , 91 ). However, an increase in Parasutterella has been found to have a protective effect against Intrahepatic Cholangiocarcinoma (ICC) ( 92 ). Parasutterella produces succinic acid and hypoxanthine ( 93 ), and is negatively correlated with levels of faecal Deoxycholic Acid (DCA) and Lithocholic Acid (LCA) ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a high-fat diet (HFD) and Clostridium difficile infection (CDI) can decrease the abundance of Parasutterella in the gut ( 90 , 91 ). However, an increase in Parasutterella has been found to have a protective effect against Intrahepatic Cholangiocarcinoma (ICC) ( 92 ). Parasutterella produces succinic acid and hypoxanthine ( 93 ), and is negatively correlated with levels of faecal Deoxycholic Acid (DCA) and Lithocholic Acid (LCA) ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified a causal association between three gut microbiota, namely Parasutterella, Dorea, and Lachnoclostridium, and PTB. Notably, Parasutterella has been found to have a causal relationship with various other conditions in several Mendelian randomization studies, including COVID-19 ( Chen H. et al, 2023 ), intrahepatic cholangiocarcinoma (ICC) ( Chen Z. et al, 2023 ), chronic kidney disease (CKD) ( Ren et al, 2023 ), and prostatitis ( Shen et al, 2024 ). Meanwhile, Dorea is associated with autism spectrum disorder (ASD) ( Li Z. et al, 2023 ), inflammatory bowel disease (IBD) ( Zhang et al, 2021 ), hypertensive disorders in pregnancy (HDP) ( Wu et al, 2023a ), polycystic ovary syndrome (PCOS) ( Min et al, 2023 ), hemorrhagic stroke ( Shen et al, 2023 ), age-related macular degeneration (AMD) ( Li and Lu, 2023 ), nicotine dependence ( Chen Y. et al, 2023 ), and insomnia ( Li Z. et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Independent sample MR, two-sample MR, multivariate MR, and bidirectional MR extensively investigate the causal association between risk factors and diseases [ 15 , 16 , 17 ]. The MR method has proven the causal association between unhealthy lifestyle choices (such as alcohol use, smoking, and obesity) and HCC [ 18 , 19 ]. Drug MR methods have garnered considerable interest for their use in drug development and predicting medication effects.…”
Section: Introductionmentioning
confidence: 99%